A medium-throughput screen for inhibitors of human metapneumovirus. (February 2019) - Becker, Jennifer C; Tollefson, Sharon J; Weaver, David; Williams, John V
Human metapneumovirus, a paramyxovirus discovered in 2001, is a major cause of lower respiratory infection in adults and children worldwide. There are no licensed vaccines or drugs for human metapneumovirus. We developed a fluorescent, cell-based medium-throughput screening assay for human metapneumovirus that captures inhibitors of all stages of the viral lifecycle except budding of progeny virus particles from the cell membrane. We optimized and validated the assay and performed a successful medium-throughput screening. A number of hits were identified, several of which were confirmed to inhibit viral replication in secondary assays. This assay offers potential to discover new antivirals for human metapneumovirus and related respiratory viruses. Compounds discovered using the medium-throughput screening may also provide useful probes of viral biology.